2010
DOI: 10.2183/pjab.86.538
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to “Key structures of bacterial peptidoglycan and lipopolysaccharide triggering the innate immune system of higher animals: Chemical synthesis and functional studies”

Abstract: Chemistry-based investigation is reviewed which led to identication of the active entities responsible for the immunostimulating potencies of peptidoglycan and lipopolysaccharide. Though these glycoconjugates which ubiquitously occur in wide range of bacteria as the essential components of their cell envelopes have long been known to enhance the immunological responses of higher animals, neither the precise chemical structures required nor the mechanism of their action had been elucidated until early 1970s. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, soluble lipid A demonstrated the properties of intact LPS, i.e., lethal toxicity and pyrogenicity induced by lipid A was comparable to their corresponding parent LPS. Furthermore, chemically synthesized E. coli lipid A has demonstrated identical endotoxic activities as natural free lipid A, further supporting lipid A as the endotoxic center of LPS [19,25,26].…”
Section: Lps Structure and Immunogenicitymentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, soluble lipid A demonstrated the properties of intact LPS, i.e., lethal toxicity and pyrogenicity induced by lipid A was comparable to their corresponding parent LPS. Furthermore, chemically synthesized E. coli lipid A has demonstrated identical endotoxic activities as natural free lipid A, further supporting lipid A as the endotoxic center of LPS [19,25,26].…”
Section: Lps Structure and Immunogenicitymentioning
confidence: 80%
“…Lipid A as well as the polysaccharide regions are able to induce potent immune responses [16,[19][20][21][22]. The lipid A component, independent of the polysaccharide portion, is responsible for various pathophysiological effects including toxicity, mitogenicity, complement reactivity [23,24], and Limulus lysate gelation [7,25,26]. Galanos et al [25] demonstrated that solubilized lipid A administered to mice and rabbits induced toxicity and pyrogenicity.…”
Section: Lps Structure and Immunogenicitymentioning
confidence: 99%